Two Types of Fuzzy Logic Controllers for the Speed Control of the Doubly-Fed Induction Machine - SAIDI, Abderazak; Farid Naceri; Lamia YOUB; Mihai CERNAT; Luis Guasch PESQUER (Advances in Electrical and Computer Engineering, 2020)
The paper presents two fuzzy logic control algorithms: type-1 and type-2. These two nonlinear techniques are used for adjust the speed control with a direct stator flux orientation control of a doubly fed induction motor. The effectiveness of the proposed control strategy is evaluated under different operating conditions such as of reference speed and for load torque step changes at nominal parameters and in the presence of parameter variation (stator resistance, rotor resistance and moment of inertia). The results of the simulation of the doubly fed induction motor velocity control have shown that fuzzy type-2 ensures better dynamic performances with respect to fuzzy type-1 control, even by parametric variations and external disturbances.